Teaching Research on Using Nano Silver Ion Dressing in Clinical Nursing of Surgically Infected Wounds: Nano Silver Ion Dressing in Nursing of Infected Wounds - Luo, Haiyan; Li, Ni; Li, Dandan; Xu, Li (Cellular and Molecular Biology, 2022)
In real life, there are few occasions where nanomaterials are exposed alone, and more often they coexist with other chemical substances. This article mainly studies the teaching of using nano-silver dressings in clinical nursing of surgically infected wounds. In this paper, the convenience sampling method is used to select 60 patients with chronic wounds as the research objects. A 160μg/mL nano-silver solution prepared with 10% fetal bovine serum DMEM culture medium was dropped on the copper net, and TEM was used for detection. The nanosilver dispersed in different dispersions was divided into 4mL EP tubes and incubated at 4°C, 25°C and 37°C for 0, 3, 12, 24, and 48 hours, and the sample at different time points were detected by a microplate reader. The maximum UV absorption peak was at 300 700nm wavelength. The micro broth dilution method was used to detect the susceptibility of different strains to Ag-PVPNPs and antibiotics. In order to study the relationship between the cytotoxicity of nano silver ion dressings and time, the nano silver ion composite dressings CZ-J1, CZ-J2, CZ-J3, CZ-J4 group samples prepared by the immersion method were selected as test samples, and the test samples were against L02 cells. At different periods, some cloth samples were taken out for anti-adhesion testing. The SPSS19.0 software was used for statistical analysis of the data, and the measurement data were expressed by the mean and standard deviation, and the homogeneity of variance was tested first. The data shows that when combined with 12.5μg/mL Ag-PVP NPs, 2μg/mL gentamicin can completely inhibit the growth of bacteria compared with 50% inhibition rate when acting alone. The results show that nano-silver activated carbon fiber dressing can effectively promote the healing of pressure sore wounds.